Oral Health-Related Quality of Life (OHRQoL) in Patients' with Dental Prosthesis - Vinod Bandela; Manay Srinivas Munisekhar; Santosh R. Patil; Anil Kumar Nagarajappa; Saif Faruqi; Kiran Kumar Metta; Mohammad Khursheed Alam; Saraswathi Kanaparthi (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the Oral Health-Related Quality of Life (OHRQoL) for post-treated fixed dental prostheses in selected sample of patients. Material and Methods: 120 patients treated with fixed dental prostheses, either single crowns or fixed partial dentures in maxillary or mandibular arches were asked to express their views about their quality of life. Patients' files were randomly selected from the archives of Department of Prosthetic Dental Sciences, College of Dentistry, Jouf University, Saudi Arabia. For this purpose, a self-structured questionnaire was prepared and their responses recorded. The responses were categorized on a 5 point scale and frequencies calculated. Results: Of 120 patients approached, 79 responded with the mean age group of 37 years. From the survey, it was noted that only three variables were statistically significant, those relating to the importance of natural teeth over fixed prostheses (p=0.046), the ability to chew all kinds of foods (p=0.021) and satisfaction with the occlusion (p<0.001). Conclusion: Oral health remains important, which directly or indirectly is related to many systemic diseases. In the present study, the majority of patients were satisfied with the treatment given.